Catheter Aspiration after Every Stage during Primary Percutaneous Angioplasty; ADMIT Trial - Turgeman, Yoav; Bushari, Limor Ilan; Antonelli, Dante; Feldman, Alexander; Yahalom, Malka; Bloch, Lev; Suleiman, Khalid (International Journal of Angiology, 2014)
We assess the epicardial and microcirculation flow characteristics, and clinical outcome by using catheter aspiration after each stage of primary percutaneous coronary intervention (PPCI). Conflicting data are reported regarding early and late benefit of using aspiration catheter in the initial phase PPCI. A total of 100 patients with ST-segment elevation acute myocardial infarction (STEMI) were included: 51 underwent PPCI without using an aspiration device (SA group) and 49 underwent PPCI by activating an aspiration catheter after each stage of procedure; wiring, ballooning and stenting, respectively (MA group). Thrombolysis in myocardial infarction (TIMI) flow grade, TIMI frame counts and myocardial blush grade (MBG) were evaluated in each group during every stage of procedure. Major adverse cardiac events were evaluated in the index hospitalization and during 30 and 180 days of follow-up.A TIMI flow grade 2–3 was more prevalent in the MA group compared with the SA group only after wiring: 65.9 versus 39.1% (p = 0.01), but TIMI frame counts were lower in the MA versus SA group throughout all procedural steps. MBG 2–3 was statistically higher in the MA group compared with the SA group mainly after wiring. After stenting there were no significant changes in both epicardial and microcirculation flow parameters. There were no significant differences between the groups in early and late clinical outcomes. Improved flow parameters were noticed in the MA group only by activating the aspiration device after wiring. This early advantage disappeared after stenting. The initial better flow characteristic in the MA group was not translated into a better early or late clinical outcome.
Keywords: primary PCI; aspiration catheter; TIMI flow; TIMI frame counts; myocardial blush grade; stenting